Behavioral Factors Influencing Pulmonary TB Prevention Among Families in Sibolahotang SAS Village, Toba, 2025 - Munarni Simatupang,; Erita Saragih, (International Journal Of Health Science, 2025)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis and is transmitted through droplets when coughing, sneezing, talking, or spitting. This study aims to determine the relationship between various factors and the behavior of TB patients in preventing transmission within their families. The study used a cross-sectional design and was conducted in Sibolahotang SAS Village, Balige Sub-district, Toba District, involving a total sample of 24 pulmonary TB patients diagnosed as smear-positive and undergoing DOTs therapy. The analyzed factors included age, gender, education, occupation, nutritional status, knowledge, housing density, and the role of health workers. The results showed that all these factors had a significant relationship with TB prevention behavior (P < 0.05), with gender being the most dominant factor ( Exp( B) = 106.648). It was concluded that various social and environmental factors influence TB prevention behavior. It is recommended that health workers become more proactive in educating patients through visual and printed media, and that health workers and cross-sector collaboration become involved in community education. TB patients are also advised to adopt healthy behaviors such as covering their mouths when coughing or sneezing, not spitting carelessly, wearing masks, maintaining proper nutrition, and adhering to treatment protocols.